Home caregiver of elderly patients with Alzheimer’s disease - Barbosa, Rafaelle Lins; Morais, Jurandir Miranda de; Resck, Zélia Marilda Rodrigues; Dázio, Eliza Maria Rezende (Rev Rene, 2012)
This is a case study with the objective of understanding the daily home care in the perspective of family caregiver of elderly with Alzheimer’s disease. The study was carried out with a family caregiver resident in the city of Alfenas-MG, Brazil, from May to June 2010, through interview with guiding question. We identified two categories: the care of the patient with Alzheimer’s and the caregiver of the patient with Alzheimer’s. We learned that the caregiver in daily care is devoted fulltime, experiences financial difficulties and of conviviality with the behavior changes of the patient, reflecting in daily overload that compromises leisure and causes health problems, seeking support in faith. Knowing the difficulties faced by the caregiver enables the health team to plan and implement support strategies for the caregiver to face the relative’s chronic condition.